Al-Najaf Al-Ashraf and the Great Iraqi Revolution in 1920 (Journal of the College of Basic Education, 2022)
The name of the honorable city of Najaf is mentioned when reviewing the political developments that Iraq witnessed throughout its various stages of history, due to its religious status and its clear cultural impact in the circles of public opinion. For several considerations, foremost of which is that it came as a response to the policy of arbitrariness, oppression, and deprivation of freedoms practiced by the British authority against the Iraqis, in addition to imposing taxes on people in various forms, and forcing the population to do forced labor.